KONSEP PEMBAGIAN HARTA BERSAMA MENURUT HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN - Beri Risky (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
This study examines the concept of shared assets in Islamic law and legislation that develops in the Indonesian state and is the result of ijtihad from scholars in Indonesia. From the results of the research it was found that, every marriage has assets that were brought and obtained before the marriage of each husband or wife. Meanwhile, joint assets in marriage or known as assets gono gini are shared prices generated through syirkah or cooperation between husband and wife. The majority of ulam said it was syirkah abdan.